Implementasi dan Tantangan Evaluasi Pembelajaran IPA di Sekolah - Ali Amrin; Pendi Pendi; Syahrul Syahrul; Isropil Siregar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Evaluation plays a crucial role in supporting the science learning process (IPA) in schools. Through evaluation, educators can assess the level of success achieved during the teaching and learning process. Although the implementation of science learning evaluations varies between schools, this diversity results in a range of evaluation outcomes. This study aims to provide an overview of the evaluation patterns used in science education at the school level. It employs a qualitative approach through a literature review (library research), utilizing techniques such as reading, note-taking, and analyzing relevant sources. Based on the findings, it can be concluded that greater attention needs to be given to the evaluation process in science learning. A well-structured and properly implemented evaluation can enhance the effectiveness of learning while encouraging teachers to continually improve the quality of their instruction. Moreover, evaluation serves to foster student motivation and engagement in learning. Therefore, considering the significant benefits of evaluation in science education, teachers are advised to optimize each stage of the evaluation process in a comprehensive and continuous manner.